In vitro investigation of the effect of photosensitizer-mediated 365-nm UV light and 630-670-nm low-energy laser irradiation on the fungal flora, Candida albicans and Fusarium spp - L. F. Troichenko; G. I. Drozhzhyna; A. L. Moloda; L. V. Dolenko (Ukrainian Society of Ophthalmologists, 2021)
Background: Infectious corneal ulcers and infectious keratitis are a major global cause of visual impairment and blindness. Although there are numerous antimicrobial agents available, novel methods should be designed to allow for fast and comprehensive microbicidal and microbistatic response on their target with minimum toxic effect to the body in order to preserve vision in patients with severe corneal infections. Purpose: To assess in vitro the antimicrobial effect of photosensitizer-mediated 365-nm ultraviolet (UV) irradiation in combination with 630-670 nm low-energy laser irradiation on the suspensions of Candida albicans and Fusarium spp. Material and Methods: The Mueller-Hinton medium was used to conduct a routine disc diffusion susceptibility test and assess the antimicrobial activity of the preparations. Methods for exerting effect on test strains of Candida albicans and Fusarium spp isolated from the conjunctival sac: The method of low-energy laser irradiation (clinically, photodynamic therapy or PDT) was as follows. A sterile disc was placed, along with test strains of microorganisms, on the surface of the medium. Methylene blue 0.1% was instilled on the surface of the sterile disc until the disc was completely covered. Thereafter, the disc was irradiated with 630-670-nm low-energy laser for three minutes. The method of UV irradiation (clinically, collagen cross-linking or CXL) was as follows. The sterile disc was placed, along with test strains of microorganisms, on the surface of the medium. Riboflavin 0.1% was instilled on the surface of the sterile disc until the disc was completely covered. Thereafter, the disc was irradiated with 365-nm UV light delivered by the UVX 2000 for 10 minutes. Results: Growth inhibition zone analysis found that Candida albicans was susceptible to PDT as well as to CXL. The diameter of the growth inhibition zone after treatment with PDT plus CXL plus fluconazole was significantly, 6.3 mm, larger than for the control disc with fluconazole. Fusarium spp was found to be susceptible to PDT plus CXL as well as to PDT plus CXL plus itraconazole, with the diameter of the growth inhibition zone being significantly, 4.2 mm and 7.8 mm, respectively, larger than for the control disc with itraconazole. Conclusion: In the in vitro experiment, the combination treatment (365-nm UV light using riboflavin 0.1% as a photosensitizer and 630-670-nm low-energy laser irradiation using methylene blue 0.1% as a photosensitizer) we proposed had a demonstrated antimicrobial effect on Candida albicans and Fusarium spp, showing fungal growth inhibition. This experimental study showed that the approach is promising and warrants further research in ophthalmology.